The influence of an educational software in the consolidation of positional numeral system (Revista de Investigaciones Universidad del Quindío, 2016)
This paper presents a methodological proposal based on a manipulative and computerized didactic material to consolidate the positional numeral system in base ten from the positional systems logic. It was established experimentally and qualitatively the effects of the proposal in the conceptual strengthening of positional numeral system. It is important to highlight the design and development of the educational software by the researches, considering a series of didactic and theoretical elements to facilitate the positional numeral system consolidation. This study evidenced that an enriching methodology based on manipulative and computerized materials is an important didactic tool in teaching and in the consolidation of positional numeral systems.
Keywords: Educational software; positional numeral system; learning consolidation